Effect of an improved molecular potential on strong-field tunneling ionization of molecules - Zhao, Song-Feng; Jin, Cheng; Le, Anh-Thu; Lin, C. D. (My University, 2010)
We study the effect of one-electron model potentials on the tunneling ionization rates of molecules in strong fields. By including electron correlation using the modified Leeuwen-Baerends (LB α) model, the binding energies of outer shells of molecules are significantly improved. However, we show that the tunneling ionization rates from the LB α do not differ much from the earlier calculations [Phys. Rev. A 81, 033423 (2010)], in which the local correlation potential was neglected.